A study on impact of training effectiveness towards on employee’s attitudes in Syarikat Perumahan Negara Berhad (SPNB) / Amira Daud - Daud, Amira (Faculty of Business and Management, 2014)
This research is to study on impact of training effectiveness towards on employee’s attitudes in Syarikat Perumahan Negara Berhad (SPNB) at Kuala Lumpur. This studies aim on employee attitudes where motivation, job satisfaction and employee effectiveness had been influenced by training. Training effectiveness important in order to increase the employees performance. Motivation, job satisfaction and employee performance will be discussed to see if it had been effect by training. In this research, it includes 90 respondent from age 20 above with different department, designation and working length. Data was collected through questionnaire that had been distribute to the respondent in SPNB. Result of the present research shows that there was significant correlation relationship between training effectiveness and employee attitudes (motivation, job satisfaction, and employee performance). This study also used regression analysis to identify which of the employees attitudes that had most been influence by training effectiveness in SPNB. This study is beneficial to others company also to increase their performance by training effectiveness. Recommendation for the future also have been discussed.